Investigating Linguistic Taboos: A Case Study of PewDiePie's Use of Forbidden Words in the "Why I Deleted the Subreddit" YouTube Video - Nur Lailatul Badriyah; Agwin Degaf; Achmad Nafis Muafi Muafi; Naila Ilma Fahmadia Fahmadia (Journal of English Language Teaching and English Linguistics, 2023)
The primary objective of this research is to uncover the utilization of taboo language in Pewdiepie's YouTube video titled "Why I deleted the subreddit." Employing a descriptive qualitative approach, a total of nine instances of taboo words were identified and categorized according to Wardhaugh's (1986) proposed typology. The most prevalent type of taboo word observed in the video was "fuck," which pertains to explicit references to sexual intercourse, accounting for 45% of the total occurrences. Following this dominant category, sexual references constituted the second most prominent type, while instances of blasphemous language, ethnic-racial insults, ancestral allusions, and vulgar terms accounted for 11% each. By analyzing the motives behind the usage of these taboo words, he was found to serve the purpose of expressing various emotions, achieving specific outcomes, and conveying the speaker's anger and frustration. Keywords: Taboo Word, PewDiePie, YouTube